SYSTEM OF MULTILEVER EDUCATION OF FUTURE TEACHERS IN UKRAINE - Prokopenko, Alona (Mountain School of Ukrainian Carpaty, 2020)
In today's globalized world, the main goal is to improve the education system to provide the country in the future with highly qualified and competitive professionals who are able to learn new approaches to professional activities, promote digitalization and use innovative technologies. Based on the analysis of scientific and pedagogical and special literature, the author considers the levels of training, namely the initial level (short cycle) of higher education; first (bachelor's) level; second (master's) level; third (educational-scientific / educational-creative) level; scientific level ". The focus is on the principles presented in the Memorandum on the Continuing Education Process of the European Union - new basic knowledge and skills for all; increase investment in human resources; innovative teaching and learning methods; new system of evaluation of received education; development of mentoring and counseling; bringing education closer to the place of residence, as well as the principles of continuous training of future teachers, namely: multilevel professional educational programs; additionality of basic and postgraduate professional education; maneuverability of professional educational programs; continuity; sequences; connection with life. These principles confirm that the level of competitiveness of the state on the world stage increasingly depends on the quality of specialists, the level of their competence. That is why it is time to use continuing education to achieve this goal and as a result it is necessary to rethink the goals and functions of education as a system, the tasks of its individual parts. The study also found that the term multilevel learning is associated with about twenty related ones such as: lifelong learning, lifelong learning, learning for the elderly, and so on.